On the temperature dependences of thermoelectric characteristics of bismuth telluride-metal transient layer with due regard for percolation effect - Gorsky , P.V.; Mytskaniuk, N.V. (Journal of Thermoelectricity, 2019)
The basic relationships are obtained by calculation, which determine the temperature dependences of thermoelectric characteristics of thermoelectric material-metal transient contact layers with due regard for percolation theory. Specific quantitative results and plots of the temperature dependences of the electrical and thermal contact resistances, the thermoEMF, the power factor, and the dimensionless thermoelectric figure of merit are given for bismuth telluride – nickel contact pair. It has been established that in the temperature range of 200-400 K on retention of uneven distribution of metal particles in transient layer and its thickness in the range of 20-150 µm, the electrical contact resistance varies from 7·10-7 to 1.9·10-5 Оhm·сm2, the thermal contact resistance – from 0.052 to 0.98 K·сm2/W, the thermoEMF– from 155 to 235 µV/K, the power factor – from 4.2·10-5 to 6.8·10-5 W/(m·K2), the dimensionless thermoelectric figure of merit – from 0.35 to 1.08. After levelling the concentration, the electrical contact resistance decreases by a factor of 1.12 – 3.6, the thermal contact resistance decreases by a factor of 1.15 – 2.08, the thermoEMF is practically unvaried, the power factor increases by a factor of 1.19 – 2.79, the dimensionless thermoelectric figure of merit increases maximum 1.2 times. Bibl. 14, Fig. 22.